Previous Article in Journal
Overview of High Energy String Scattering Amplitudes and Symmetries of String Theory

Erratum published on 17 December 2019, see Symmetry 2019, 11(12), 1530.
Font Type:
Arial Georgia Verdana
Font Size:
Aa Aa Aa
Line Spacing:
Column Width:
Background:
Article

# Degenerate Stirling Polynomials of the Second Kind and Some Applications

by
Taekyun Kim
1,*,
Dae San Kim
2,*,
Han Young Kim
1 and
Jongkyum Kwon
3,*
1
Department of Mathematics, Kwangwoon University, Seoul 139-701, Korea
2
Department of Mathematics, Sogang University, Seoul 121-742, Korea
3
Department of Mathematics Education and ERI, Gyeongsang National University, Jinju 52828, Korea
*
Authors to whom correspondence should be addressed.
Symmetry 2019, 11(8), 1046; https://doi.org/10.3390/sym11081046
Submission received: 20 July 2019 / Revised: 10 August 2019 / Accepted: 13 August 2019 / Published: 14 August 2019

## Abstract

:
Recently, the degenerate $λ$-Stirling polynomials of the second kind were introduced and investigated for their properties and relations. In this paper, we continue to study the degenerate $λ$-Stirling polynomials as well as the r-truncated degenerate $λ$-Stirling polynomials of the second kind which are derived from generating functions and Newton’s formula. We derive recurrence relations and various expressions for them. Regarding applications, we show that both the degenerate $λ$-Stirling polynomials of the second and the r-truncated degenerate $λ$-Stirling polynomials of the second kind appear in the expressions of the probability distributions of appropriate random variables.

## 1. Introduction

For $n ≥ 0$, the Stirling numbers of the second kind are defined as (see [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26])
$x n = ∑ k = 0 n S 2 ( n , k ) ( x ) k ,$
where $( x ) 0 = 1 , ( x ) n = x ( x − 1 ) ⋯ ( x − n + 1 ) , ( n ≥ 1 )$.
From (1), we note that the generating function for $S 2 ( n , k )$ is given by (see [8,9,23,26])
$1 k ! ( e t − 1 ) k = ∑ n = k ∞ S 2 ( n , k ) t n n ! , ( k ≥ 0 ) .$
For $λ ∈ R$, the degenerate exponential function is defined by (see [10,11,27,28])
$e λ x ( t ) = ( 1 + λ t ) x λ , e λ ( t ) = e λ 1 ( t ) = ( 1 + λ t ) 1 λ .$
In view of (2), the degenerate λ-Stirling polynomials of the second kind are defined by the generating function
$1 k ! ( e λ ( t ) − 1 ) k e λ x ( t ) = ∑ n = k ∞ S 2 , λ ( x ) ( n , k ) t n n ! ,$
where $x ∈ R$ and k is a nonnegative integer, (see [10,11]).
When $x = 0$, $S 2 , λ ( 0 ) ( n , k ) = S 2 , λ ( n , k )$ are called the degenerate $λ$-Stirling numbers of the second kind. Note that $lim λ → 0 S 2 , λ ( n , k ) = S 2 ( n , k ) , ( n , k ≥ 0 )$.
By letting $λ → 0$ in (4), we have the generating function for the Stirling polynomials of the second kind $S 2 ( x ) ( n , k )$ (see [11,13,14,22]):
$1 k ! ( e t − 1 ) k e x t = ∑ n = k ∞ S 2 ( x ) ( n , k ) t n n ! .$
Let X be a discrete random variable with probability mass function $P [ X = x ] = p ( x )$. Then, the probability generating function of X is given by (see [4,17,18,20,22])
$G ( t ) = E [ t X ] = ∑ x = 0 ∞ t x p ( x ) .$
Suppose that $X = ( X 1 , X 2 , ⋯ , X k )$ is a discrete random variable taking values in the k-dimensional nonnegative integer lattice. Then, the probability generating function of X is defined as (see [4])
$G ( t ) = G ( t 1 , t 2 , ⋯ , t k ) = E [ t 1 X 1 t 2 X 2 ⋯ t k X k ] = ∑ x 1 , x 2 , ⋯ , x k = 0 ∞ t 1 x 1 t 2 x 2 ⋯ t k x k p ( x 1 , x 2 , ⋯ x k ) ,$
where $p ( x 1 , x 2 , ⋯ x k )$ is the probability mass function of $X = ( X 1 , X 2 , ⋯ , X k )$.
X is the random variable with the zero-truncated Poisson distribution with parameter $λ$ if the probability mass function of X is (see [4,17,18,20,22])
$P [ X = x ] = p ( x ) = 1 1 − e − λ e − λ λ x x ! ,$
where x is a positive integer.
For $r ∈ N$, X is the random variable with r-truncated Poisson distribution with parameter $λ$ if the probability mass function of X is
$P [ X = x ] = p ( x ) = C ( λ , r ) e − λ λ x x ! ,$
where $C ( λ , r ) = ( 1 − e − λ ∑ x = 0 r − 1 λ x x ! ) − 1$.
In this paper, we study the degenerate $λ$-Stirling polynomials, as a continuation of the previous work in [10], and also the r-truncated degenerate $λ$-Stirling polynomials of the second kind which are derived from generating functions and Newton’s formula. We derive recurrence relations and various expressions for them. As applications, we show that both the degenerate $λ$-Stirling polynomials of the second kind and the r-truncated degenerate $λ$-Stirling polynomials of the second kind appear in the expressions of the probability distributions of appropriate random variables.

## 2. The Degenerate $λ$-Stirling Polynomials of the Second Kind

Let $x , t$ be real numbers and let n be a nonnegative integer. The difference operator ▵ is defined by $▵ f ( x ) = f ( x + 1 ) − f ( x )$. It is easy to show that
$( I + ▵ ) n f ( 0 ) = f ( n ) = ∑ k = 0 n n k ▵ k f ( 0 ) .$
From (10), we can derive Newton’s formula which is given by
$f ( t ) = ∑ k = 0 ∞ t k ▵ k f ( 0 ) .$
Let us take $f ( t ) = ( t + x ) n , λ , ( n ≥ 0 )$. Then, by (11), we get
$( t + x ) n , λ = ∑ k = 0 ∞ t k ▵ k ( t + x ) n , λ t = 0 = ∑ k = 0 n t k ▵ k ( t + x ) n , λ t = 0 = ∑ k = 0 n 1 k ! ▵ k ( t + x ) n , λ t = 0 ( t ) k .$
Here, the generalized factorial sequence $( x ) n , λ$ is given by
$( x ) 0 , λ = 1 , ( x ) n , λ = x ( x − λ ) ⋯ ( x − ( n − 1 ) λ ) , ( n ≥ 1 ) .$
Let
$S 2 , λ ( x ) ( n , k ) = 1 k ! ▵ k ( t + x ) n , λ t = 0 = 1 k ! ▵ k ( x ) n , λ , ( n , k ≥ 0 ) .$
Then, by (12) and (14), we get
$( t + x ) n , λ = ∑ k = 0 n S 2 , λ ( x ) ( n , k ) ( t ) k , ( n ≥ 0 ) .$
In (18) below, we show that the $S 2 , λ ( x ) ( n , k )$ in (14) or (15) is really the degenerate $λ$-Stirling polynomials of the second kind defined in (4).
Using (13), (15), and interchanging the order of summations, we note that
$e λ x + y ( t ) = ∑ n = 0 ∞ ( x + y ) n , λ t n n ! = ∑ n = 0 ∞ ∑ k = 0 n S 2 , λ ( x ) ( n , k ) ( y ) k t n n ! = ∑ k = 0 ∞ ∑ n = k ∞ S 2 , λ ( x ) ( n , k ) t n n ! ( y ) k .$
On the other hand,
$e λ x + y ( t ) = e λ x ( t ) ( e λ ( t ) − 1 + 1 ) y = ∑ k = 0 ∞ 1 k ! ( e λ ( t ) − 1 ) k e λ x ( t ) ( y ) k .$
By (16) and (17), we get
$1 k ! ( e λ ( t ) − 1 ) k e λ x ( t ) = ∑ n = k ∞ S 2 , λ ( x ) ( n , k ) t n n ! , ( k ≥ 0 ) .$
Thus, we have shown that the definition of the degenerate $λ$-Stirling polynomials of the second kind can be given as (14) or equivalently (15) or equivalently (18).
Note that
$S 2 , λ ( x ) ( 0 , 0 ) = 1 , S 2 , λ ( x ) ( n , 0 ) = ( x ) n , λ , S 2 , λ ( x ) ( 0 , k ) = 0 , ( k ≠ 0 ) .$
We would like to derive a recurrence relation for the degenerate $λ$-Stirling polynomials of the second kind. Now, we observe that
$∑ k = 0 n + 1 S 2 , λ ( x ) ( n + 1 , k ) ( t ) k = ( t + x ) n + 1 , λ = ( t + x ) n , λ ( t + x − n λ ) = t ∑ k = 0 n S 2 , λ ( x ) ( n , k ) ( t ) k + ( x − n λ ) ∑ k = 0 n S 2 , λ ( x ) ( n , k ) ( t ) k = t ∑ k = 1 n + 1 S 2 , λ ( x ) ( n , k − 1 ) ( t ) k − 1 + ( x − n λ ) ∑ k = 0 n S 2 , λ ( x ) ( n , k ) ( t ) k = ∑ k = 1 n + 1 ( t − k + 1 + k − 1 ) S 2 , λ ( x ) ( n , k − 1 ) ( t ) k − 1 + ( x − n λ ) ∑ k = 0 n S 2 , λ ( x ) ( n , k ) ( t ) k = ∑ k = 1 n + 1 S 2 , λ ( x ) ( n , k ) ( t ) k + ∑ k = 0 n k S 2 , λ ( x ) ( n , k ) ( t ) k + ( x − n λ ) ∑ k = 0 n S 2 , λ ( x ) ( n , k ) ( t ) k = ∑ k = 0 n + 1 S 2 , λ ( x ) ( n , k − 1 ) + ( k + x − n λ ) S 2 , λ ( x ) ( n , k ) ( t ) k .$
Therefore, by comparing the coefficients on both sides of (20), we obtain the following theorem.
Theorem 1.
Let $n , k$ be nonnegative integers. Then, we have
$S 2 , λ ( x ) ( n + 1 , k ) = S 2 , λ ( x ) ( n , k − 1 ) + ( k + x − n λ ) S 2 , λ ( x ) ( n , k ) , ( n ≥ k − 1 ) .$
Note that
$S 2 , λ ( x ) ( n , k ) = 0 , i f k > n , S 2 , λ ( x ) ( n , n ) = 1 .$
From (14), we have
$S 2 , λ ( 0 ) ( n , k ) = 1 k ! ▵ k ( 0 ) n , λ = S 2 , λ ( n , k ) , ( n , k ≥ 0 ) .$
Here, we want to derive an explicit expression for the degenerate $λ$-Stirling polynomials of the second kind. By (18), we get
$∑ n = k ∞ S 2 , λ ( x ) ( n , k ) t n n ! = 1 k ! e λ x ( t ) ( e λ ( t ) − 1 ) k = 1 k ! ∑ m = 0 ∞ ( x ) m , λ m ! t m ∑ l = k ∞ ∑ l 1 + ⋯ + l k = l ( 1 ) l 1 , λ ( 1 ) l 2 , λ ⋯ ( 1 ) l k , λ l 1 ! l 2 ! ⋯ l k ! t l = ∑ n = k ∞ n ! k ! ∑ l = k n ( x ) n − l , λ ( n − l ) ! ∑ l 1 + ⋯ + l k = l ( 1 ) l 1 , λ ( 1 ) l 2 , λ ⋯ ( 1 ) l k , λ l 1 ! l 2 ! ⋯ l k ! t n n ! ,$
where all $l j$’s are positive integers.
Therefore, by comparing the coefficients on both sides of (22), we obtain the following theorem.
Theorem 2.
For $n , k ∈ N ∪ { 0 }$, with $n ≥ k$, we have
$S 2 , λ ( x ) ( n , k ) = n ! k ! ∑ l = k n ( x ) n − l , λ ( n − l ) ! ∑ l 1 + ⋯ + l k = l ( 1 ) l 1 , λ ( 1 ) l 2 , λ ⋯ ( 1 ) l k , λ l 1 ! l 2 ! ⋯ l k ! ,$
where in the inner sum, all $l j$’s are positive integers.
Next, we want to derive more explicit expressions for the degenerate $λ$-Stirling polynomials of the second kind.
From (18), we note that
$∑ n = k ∞ S 2 , λ ( x ) ( n , k ) t n n ! = e λ x ( t ) 1 k ! ( e λ ( t ) − 1 ) k = ∑ m = 0 ∞ ( x ) m , λ m ! t m ∑ l = k ∞ S 2 , λ ( l , k ) t l l ! = ∑ n = k ∞ ∑ l = k n n l S 2 , λ ( l , k ) ( x ) n − l , λ t n n ! .$
On the other hand, we have
$1 k ! e λ x ( t ) ( e λ ( t ) − 1 ) k = 1 k ! ∑ l = 0 k k l ( − 1 ) k − l e λ l + x ( t ) = ∑ n = 0 ∞ 1 k ! ∑ l = 0 k k l ( − 1 ) k − l ( l + x ) n , λ t n n ! .$
Therefore, by (23) and (24), we obtain the following theorem.
Theorem 3.
Let $n , k$ be nonnegative integers with $n ≥ k$. Then, we have
$S 2 , λ ( x ) ( n , k ) = ∑ l = k n n l S 2 , λ ( n , k ) ( x ) n − l , λ = 1 k ! ∑ l = 0 k k l ( − 1 ) k − l ( l + x ) n , λ .$
For $r ∈ N$, we define the r-truncated degenerate λ-Stirling polynomials of the second kind, $S 2 , λ ( x ) ( n , k | r )$, by the generating function
$e λ x ( t ) 1 k ! e λ ( t ) − ∑ j = 0 r − 1 ( 1 ) j , λ j ! t j k = ∑ n = r k ∞ S 2 , λ ( x ) ( n , k | r ) t n n ! .$
Now, we derive an explicit expression for the r-truncated degenerate $λ$-Stirling polynomials of the second kind. From (25), we note that
$∑ n = r k ∞ S 2 , λ ( x ) ( n , k | r ) t n n ! = e λ x ( t ) 1 k ! e λ ( t ) − ∑ j = 0 r − 1 ( 1 ) j , λ j ! t j k = 1 k ! ∑ m = 0 ∞ ( x ) m , λ t m m ! ∑ n = r k ∞ ∑ l 1 + ⋯ + l k = l ( 1 ) l 1 , λ ( 1 ) l 2 , λ ⋯ ( 1 ) l k , λ l 1 ! l 2 ! ⋯ l k ! t l = n ! k ! ∑ l = r k ∞ ∑ l = r k n ( x ) n − l , λ ( n − l ) ! ∑ l 1 + ⋯ + l k = l ( 1 ) l 1 , λ ( 1 ) l 2 , λ ⋯ ( 1 ) l k , λ l 1 ! l 2 ! ⋯ l k ! t n n ! ,$
where all $l j$’s are integers with $l j ≥ r$.
Therefore, by comparing the coefficients on both sides of (26), we obtain the following theorem.
Theorem 4.
Let $n , k$ be nonnegative integers. Then, we have
$S 2 , λ ( x ) ( n , k | r ) = n ! k ! ∑ l = r k n ( x ) n − l , λ ( n − l ) ! ∑ l 1 + ⋯ + l k = l ( 1 ) l 1 , λ ( 1 ) l 2 , λ ⋯ ( 1 ) l k , λ l 1 ! l 2 ! ⋯ l k ! , ( n ≥ r k ) ,$
where the inner sum runs over all integers $l 1 , ⋯ , l k ≥ r$, with $l 1 + ⋯ + l k = l$.
Remark 1.
When $x = 0$, $S 2 , λ ( 0 ) ( n , k | r ) = S 2 , λ ( n , k | r )$ are called the r-truncated degenerate λ-Stirling numbers of the second kind.
From (25), we note that
$∑ n = r k ∞ S 2 , λ ( x ) ( n , k | r ) t n n ! = e λ x ( t ) 1 k ! e λ ( t ) − ∑ j = 0 r − 1 ( 1 ) j , λ j ! t j k = ∑ m = 0 ∞ ( x ) m , λ m ! t m ∑ l = r k ∞ S 2 , λ ( l , k | r ) t l l ! = ∑ n = r k ∞ ∑ l = r k n n l S 2 , λ ( l , k | r ) ( x ) n − l , λ t n n ! .$
Thus, by (27), we get
$S 2 , λ ( x ) ( n , k | r ) = 0 , i f n < k r ,$
and
$S 2 , λ ( x ) ( n , k | r ) = ∑ l = r k n n l S 2 , λ ( l , k | r ) ( x ) n − l , λ , i f n ≥ k r .$
Next, we deduce a recurrence relation for the r-truncated degenerate $λ$-Stirling polynomials of the second kind. Now, we observe that
$∑ n = r k ∞ S 2 , λ ( x ) ( n , k | r + 1 ) t n n ! = ∑ n = k ( r + 1 ) ∞ S 2 , λ ( x ) ( n , k | r + 1 ) t n n ! = e λ x ( t ) k ! e λ ( t ) − ∑ j = 0 r ( 1 ) j , λ j ! t j k = 1 k ! e λ x ( t ) e λ ( t ) − ∑ j = 0 r − 1 ( 1 ) j , λ j ! t j − ( 1 ) r , λ r ! t r k = 1 k ! e λ x ( t ) ∑ l = 0 k k l e λ ( t ) − ∑ j = 0 r − 1 ( 1 ) j , λ j ! t j k − l ( − 1 ) l ( 1 ) j , λ l ( r ! ) l t r l$
$= ∑ l = 0 k ( − 1 ) l ( 1 ) j , λ l l ! ( r ! ) l t r l 1 ( k − l ) ! e λ x ( t ) e λ ( t ) − ∑ j = 0 r − 1 ( 1 ) j , λ j ! t j k − l = ∑ l = 0 k ( − 1 ) l ( 1 ) j , λ l l ! ( r ! ) l t r l ∑ n = ( k − l ) r ∞ S 2 , λ ( x ) ( n , k − l | r ) t n n ! = ∑ l = 0 k ( − 1 ) l ( 1 ) j , λ l l ! ( r ! ) l t r l ∑ n = k r ∞ S 2 , λ ( x ) ( n − l r , k − l | r ) t n − l r ( n − l r ) ! = ∑ n = k r ∞ ∑ l = 0 k ( − 1 ) l ( 1 ) j , λ l l ! ( n ) l r ( r ! ) l S 2 , λ ( x ) ( n − l r , k − l | r ) t n n ! .$
Comparing the coefficients on both sides of (30), we obtain the following theorem.
Theorem 5.
Let $n , k$ be nonnegative integers. For $n ≥ k r$, we have
$S 2 , λ ( x ) ( n , k | r + 1 ) = ∑ l = 0 k ( − 1 ) l ( 1 ) j , λ l l ! ( n ) l r ( r ! ) l S 2 , λ ( x ) ( n − l r , k − l | r ) .$
Definition 1.
We call a random variable Y the degenerate Poisson random variable with parameter α if the probability mass function of Y is given by
$P [ Y = y | Y ≥ 0 ] = p ( y ) = e λ − 1 ( α ) α y ( 1 ) y , α y ! .$
X is called the zero-truncated degenerate Poisson random variable with parameter α if the probability mass function of X is given by
$P [ X = x | X > 0 ] = p ( x ) = 1 1 − e λ − 1 ( α ) e λ − 1 ( α ) ( 1 ) x , α α x x ! .$
Note that
$∑ y = 0 ∞ p ( y ) = e λ − 1 ( α ) ∑ y = 0 ∞ α y ( 1 ) y , α y ! = 1 ,$
and
$∑ x = 1 ∞ p ( x ) = 1 e λ ( α ) − 1 ∑ x = 1 ∞ ( 1 ) x , α α x x ! = 1 .$
As an application, we show that the degenerate $λ$-Stirling polynomials of the second kind appear in the expression of the probability distributions of appropriate random variables. Suppose that $X 1 , X 2 , ⋯ , X k$ are independent random variables with degenerate zero-truncated Poisson distribution with parameter $α$ and that Y is another random variable with degenerate Poisson distribution with parameter $α$. If Y is independent of $X = X 1 + X 2 + ⋯ + X k$, then we have
$E [ t X + Y ] = E [ t X ] E [ t Y ] = ∏ j = 1 k E [ t X j ] E [ t Y ] .$
From (32), we note that
$E [ t X j ] = ∑ x = 1 ∞ P [ X j = x ] t x = 1 e λ ( α ) − 1 ∑ x = 1 ∞ ( 1 ) x , α α x x ! t x = 1 e λ ( α ) − 1 ( e λ ( α t ) − 1 ) .$
By (33), we get
$∏ j = 1 k E [ t X j ] = 1 e λ ( α ) − 1 k e λ ( α t ) − 1 k = k ! ( e λ ( α ) − 1 ) k 1 k ! e λ ( α t ) − 1 k .$
By (31), we get
$E [ t Y ] = ∑ y = 0 ∞ P [ Y = y ] t y = e λ − 1 ( α ) ∑ y = 0 ∞ α y ( 1 ) y , α y ! t y = e λ − 1 ( α ) e λ ( α t ) .$
From (34) and (35), we have
$E [ t X + Y ] = ∏ j = 1 k E [ t X j ] E [ t Y ] = k ! e λ ( α ) ( e λ ( α ) − 1 ) k 1 k ! e λ ( α t ) − 1 k e λ ( α t ) = ∑ n = k ∞ k ! e λ ( α ) ( e λ ( α ) − 1 ) k S 2 , λ ( 1 ) ( n , k ) α n t n n ! .$
On the other hand,
$E [ t X + Y ] = ∑ n = k ∞ P [ X + Y = n ] t n .$
Therefore, by (36) and (37), we obtain the following theorem.
Theorem 6.
Suppose that $X 1 , X 2 , ⋯ , X k$ are independent random variables with degenerate zero-truncated Poisson distribution with parameter α, and Y is another random variable with degenerate Poisson distribution with parameter α. If Y is independent of $X = X 1 + X 2 + ⋯ + X k$, then the probability distribution of $X + Y$ is given by
$P [ X + Y = n ] = k ! e λ ( α ) ( e λ ( α ) − 1 ) k α n n ! S 2 , λ ( 1 ) ( n , k ) ,$
where $n ≥ k$.
For $r ∈ N$, we define X as the random variable with the r-truncated degenerate Poisson distribution with parameter $α$ if the probability mass function of X is given by
$P [ X = x | X ≥ r ] = p ( x ) = e λ − 1 ( α ) 1 − e λ − 1 ( α ) ∑ x = 0 r − 1 α x ( 1 ) x , α x ! α x ( 1 ) x , α x ! .$
As an application, we show that the r-truncated degenerate $λ$-Stirling polynomials of the second kind appear in the expression of the probability distribution of appropriate random variables. Suppose that $X 1 , X 2 , ⋯ , X k$ are independent random variables with r-truncated degenerate Poisson distribution with parameter $α$, and Y is a random variable with degenerate Poisson distribution with parameter $α$. If Y is independent of $X = X 1 + X 2 + ⋯ + X k$, then we have
$E [ t X + Y ] = E [ t X ] E [ t Y ] = ∏ j = 1 k E [ t X j ] E [ t Y ] .$
From (38), we have
$E [ t X j ] = ∑ n = r ∞ P [ X j = n ] t n = ∑ n = r ∞ 1 e λ ( α ) − ∑ j = 0 r − 1 ( 1 ) j , α α j j ! α n ( 1 ) n , α n ! t n = 1 e λ ( α ) − ∑ j = 0 r − 1 ( 1 ) j , α α j j ! e λ ( α t ) − ∑ j = 0 r − 1 ( 1 ) j , α α j j ! t j = C λ ( λ , r ) e λ ( α t ) − ∑ j = 0 r − 1 ( 1 ) j , α α j j ! t j ,$
where $C λ ( λ , r ) = 1 e λ ( α ) − ∑ j = 0 r − 1 ( 1 ) j , α α j j !$.
By (40), we get
$∏ j = 1 k E [ t X j ] = C λ k ( λ , r ) e λ ( α t ) − ∑ j = 0 r − 1 ( 1 ) j , α α j j ! t j k .$
From (35) and (41), we note that
$E [ t X + Y ] = k ! C λ k ( λ , r ) 1 k ! e λ ( α t ) − ∑ j = 0 r − 1 ( 1 ) j , α α j j ! t j k e λ − 1 ( α ) e λ ( α t ) = k ! C λ k ( λ , r ) e λ − 1 ( α ) 1 k ! e λ ( α t ) − ∑ j = 0 r − 1 ( 1 ) j , α α j j ! t j k e λ ( α t ) = ∑ n = k r ∞ k ! C λ k ( λ , r ) e λ ( α ) S 2 , λ ( 1 ) ( n , k | r ) α n n ! t n .$
On the other hand,
$E [ t X + Y ] = ∑ n = k ∞ P [ X + Y = n ] t n .$
Therefore, by (41) and (42), we obtain the following theorem.
Theorem 7.
For $r ∈ N$, suppose that $X 1 , X 2 , ⋯ , X k$ are independent random variables with r-truncated degenerate Poisson distribution with parameter α and that Y is a random variable with degenerate Poisson distribution with parameter α. If Y is independent of $X = X 1 + X 2 + ⋯ + X k$, then the probability distribution of $X + Y$ is given by
$P [ X + Y = n ] = k ! C λ k ( λ , r ) e λ ( α ) S 2 , λ ( 1 ) ( n , k | r ) α n n ! ,$
where $n ≥ k r$.
Remark 2.
Suppose that $X 1 , X 2 , ⋯ , X k$ are independent random variables with r-truncated degenerate Poisson distribution with parameter α, and $Y 1 , Y 2 , ⋯ , Y m$ are independent random variables with degenerate Poisson distribution with parameter α. If $Y = Y 1 + Y 2 + ⋯ + Y m$ is independent of $X = X 1 + X 2 + ⋯ + X k$, then we have
$E [ t X + Y ] = E [ t X ] E [ t Y ] = ∏ j = 1 k E [ t X j ] ∏ i = 1 m E [ t Y i ] .$
From (35) and (40), we have
$E [ t X + Y ] = k ! C λ k ( λ , r ) 1 k ! e λ ( α t ) − ∑ j = 0 r − 1 ( 1 ) j , α α j j ! t j k e λ − m ( α ) e λ m ( α t ) = k ! C λ k ( λ , r ) e λ m ( α ) 1 k ! e λ ( α t ) − ∑ j = 0 r − 1 ( 1 ) j , α α j j ! t j k e λ m ( α t ) = ∑ n = k r ∞ k ! C λ k ( λ , r ) e λ m ( α ) S 2 , λ ( m ) ( n , k | r ) α n n ! t n .$
On the other hand,
$E [ t X + Y ] = ∑ n = k ∞ P [ X + Y = n ] t n .$
From (44) and (45), we obtain the probability distribution of $X + Y$ to be
$P [ X + Y = n ] = k ! C λ k ( λ , r ) e λ m ( α ) S 2 , λ ( m ) ( n , k | r ) α n n ! ,$
where $n ≥ k r$.

## 3. Conclusions

The degenerate $λ$-Stirling polynomials of the second kind were introduced and investigated for their properties and relations in [10]. In this paper, we continued to study the degenerate $λ$-Stirling polynomials as well as the r-truncated degenerate $λ$-Stirling polynomials of the second kind which are derived from generating functions and Newton’s formula. We derived recurrence relations and various expressions for them. Regarding applications, we showed that both the degenerate $λ$-Stirling polynomials of the second kind and the r-truncated degenerate $λ$-Stirling polynomials of the second kind appear in the expressions of the probability distributions of appropriate random variables. Indeed, the degenerate $λ$-Stirling polynomials of the second kind (more precisely, the value at 1 of them) appear in the probability distribution of the random variable given as the sum of a finite number of random variables with degenerate zero-truncated Poisson distributions and a random variable with degenerate Poisson distribution, all having the same parameter. Similarly, the r-truncated degenerate $λ$-Stirling polynomials of the second kind (more precisely, the value at 1 of them) appear in the probability distribution of the random variable given as the sum of a finite number of random variables with r-truncated Poisson distributions and a random variable with degenerate Poisson distribution, all having the same parameter. As one of our future projects, we will continue to pursue this line of research, namely study certain special polynomials and numbers and their applications as regards probability theory.

## Author Contributions

Conceptualization, D.S.K. and T.K.; Formal analysis, D.S.K., J.K. and T.K.; Funding acquisition, J.K.; Investigation, D.S.K., H.Y.K. and T.K.; Methodology, D.S.K. and T.K.; Project administration, T.K.; Software, J.K.; Supervision, D.S.K. and T.K.; Validation, D.S.K., H.Y.K., J.K. and T.K.; Visualization, H.Y.K. and J.K.; Writing—original draft, T.K.; Writing—review & editing, D.S.K., H.Y.K. and T.K.

## Funding

This work was supported by the National Research Foundation of Korea (NRF) grant funded by the Korea government (MEST) (No. 2017R1E1A1A03070882).

## Acknowledgments

The authors would like to thank the referees for their valuable comments and suggestions that improved the original manuscript greatly in its present form.

## Conflicts of Interest

The authors declare that they have no competing interests.

## References

1. Araci, S.; Acikgoz, M. A note on the Frobenius-Euler numbers and polynomials associated with Bernstein polynomials. Adv. Stud. Contemp. Math. (Kyungshang) 2012, 22, 399–406. [Google Scholar]
2. Carlitz, L. Degenerate Stirling, Bernoulli and Eulerian numbers. Util. Math. 1979, 15, 51–88. [Google Scholar]
3. Dolgy, D.V.; Kim, T. Some explicit formulas of degenerate Stirling numbers associated with the degenerate special numbers and polynomials. Proc. Jangjeon Math. Soc. 2018, 21, 309–317. [Google Scholar]
4. Feller, W. An Introduction to Probability Theory and Its Application; John Wiley: Hoboken, NJ, USA, 1970. [Google Scholar]
5. He, Y.; Pan, J. Some recursion formulae for the number of derangements and Bell numbers. J. Math. Res. Appl. 2016, 36, 15–22. [Google Scholar]
6. Howard, F.T. Bell polynomials and degenerate Stirling numbers. Rend. Sem. Mat. Univ. Padova. 1979, 61, 203–219. [Google Scholar]
7. Jeong, J.; Rim, S.-H.; Kim, B.M. On finite-times degenerate Cauchy numbers and polynomials. Adv. Differ. Equ. 2015, 2015, 321. [Google Scholar] [CrossRef] [Green Version]
8. Kim, D.S.; Kim, T.; Jang, G.-W. A note on degenerate Stirling numbers of the first kind. Proc. Jangjeon Math. Soc. 2018, 21, 393–404. [Google Scholar]
9. Kim, D.S.; Dolgy, D.V.; Kim, D.; Kim, T. Some identities on r-central factorial numbers and r-central Bell polynomials. Adv. Differ. Equ. 2019, 2019, 245. [Google Scholar] [CrossRef]
10. Kim, T. A note on degenerate Stirling polynomials of the second kind. Proc. Jangjeon Math. Soc. 2017, 20, 319–331. [Google Scholar]
11. Kim, T.; Kim, D.S.; Jang, G.-W. Extended Stirling polynomials of the second kind and extended Bell polynomials. Proc. Jangjeon Math. Soc. 2017, 20, 365–376. [Google Scholar]
12. Kim, T.; Jang, G.-W. A note on degenerate gamma function and degenerate Stirling number of the second kind. Adv. Stud. Contemp. Math. (Kyungshang) 2018, 28, 207–214. [Google Scholar]
13. Kim, T.; Yao, Y.; Kim, D.S.; Kwon, H.-I. Some identities involving special numbers and moments of random variables. Rocky Mt. J. Math. 2019, 49, 521–538. [Google Scholar] [CrossRef] [Green Version]
14. Kim, T.; Kim, D.S. Extended Stirling numbers of the first kind associated with Daehee numbers and polynomials. Adv. Stud. Contemp. Math. (Kyungshang) 2018, 28, 127–138. [Google Scholar] [CrossRef]
15. Kim, T.; Kim, D.S.; Kwon, H.-I. A note on degenerate Stirling numbers and their applications. Proc. Jangjeon Math. Soc. 2018, 21, 195–203. [Google Scholar]
16. Kim, T.; Kim, D.S. On λ-Bell polynomials associated with umbral calculus. Russ. J. Math. Phys. 2017, 24, 69–78. [Google Scholar] [CrossRef]
17. Koutras, M. Non-central stirling numbers and some applications. Discret. Math. 1982, 42, 73–89. [Google Scholar] [CrossRef] [Green Version]
18. Ross, S.M. Introduction to Probability Models; Academic Press: Cambridge, MA, USA, 2007. [Google Scholar]
19. Brualdi, R.A. Introductory Combinatorics; China Machine Press: Beijing, China, 2009. [Google Scholar]
20. Kotz, S.; Kozubowski, T.J.; Podgorski, K. The Laplace Distribution and Generalizations; Birkhäuser Boston, Inc.: Boston, MA, USA, 2001. [Google Scholar]
21. Kim, D.S.; Kim, H.Y.; Kim, D.; Kim, T. Identities of symmetry for type 2 Bernoulli and Euler polynomials. Symmetry 2019, 11, 613. [Google Scholar] [CrossRef]
22. Dolgy, D.V.; Kim, D.S.; Kwon, J.; Kim, T. Some identities of ordinary and degenerate Bernoulli numbers and polynomials. Symmetry 2019, 11, 847. [Google Scholar] [CrossRef]
23. Kim, D.S.; Dolgy, D.V.; Kwon, J.; Kim, T. Note on type 2 degenerate q-Bernoulli polynomials. Symmetry 2019, 11, 914. [Google Scholar] [CrossRef]
24. Kim, T.; Kim, D.S. Degenerate Bernstein polynomials. Rev. R. Acad. Cienc. Exactas Fís. Nat. Ser. A Mat. RACSAM 2019, 113, 2913–2920. [Google Scholar] [CrossRef]
25. Kim, T.; Kim, D.S. A note on type 2 Changhee and Daehee polynomials. Rev. R. Acad. Cienc. Exactas Fís. Nat. Ser. A Mat. RACSAM 2019, 113, 2783–2791. [Google Scholar] [CrossRef]
26. Kim, T.; Kim, D.S. Degenerate central Bell numbers and polynomials. Rev. R. Acad. Cienc. Exactas Fís. Nat. Ser. A Mat. RACSAM 2019, 113, 2507–2513. [Google Scholar] [CrossRef]
27. Kim, T.; Kim, D.S. Identities for degenerate Bernoulli polynomials and Korobov polynomials of the first kind. Sci. China Math. 2019, 62, 999–1028. [Google Scholar] [CrossRef]
28. Kim, T.; Kim, D.S. Degenerate Laplace transform and degenerate gamma function. Russ. J. Math. Phys. 2017, 24, 241–248. [Google Scholar] [CrossRef] [Green Version]

## Share and Cite

MDPI and ACS Style

Kim, T.; Kim, D.S.; Kim, H.Y.; Kwon, J. Degenerate Stirling Polynomials of the Second Kind and Some Applications. Symmetry 2019, 11, 1046. https://doi.org/10.3390/sym11081046

AMA Style

Kim T, Kim DS, Kim HY, Kwon J. Degenerate Stirling Polynomials of the Second Kind and Some Applications. Symmetry. 2019; 11(8):1046. https://doi.org/10.3390/sym11081046

Chicago/Turabian Style

Kim, Taekyun, Dae San Kim, Han Young Kim, and Jongkyum Kwon. 2019. "Degenerate Stirling Polynomials of the Second Kind and Some Applications" Symmetry 11, no. 8: 1046. https://doi.org/10.3390/sym11081046

Note that from the first issue of 2016, this journal uses article numbers instead of page numbers. See further details here.